Utilization of Artificial Intelligence Technology in Transforming Islamic Education Learning Based on Spiritual and Humanistic Values - Septi Ariani; Rista Yuni Sarah; Lasmi Eva Salsabillah; Rupiyanto Rupiyanto; Ahmad Syarifuddin Zuhri (BASICA, 2025)
This study aims to analyze the use of Artificial Intelligence in transforming Islamic education learning based on spiritual and humanistic values. The development of digital technology has brought about major changes in the world of education, including in the learning process of Islamic education. The presence of Artificial Intelligence provides opportunities to create learning that is more innovative, interactive, flexible, and adaptive to the needs of students. However, the implementation of AI also gives rise to various problems, such as technological dependence, decreased humanistic interaction, weakened critical thinking skills, and the potential for a reduction in spiritual values ​​in the learning process. This study uses a qualitative approach with library research. Data were obtained from scientific journals, books, and various relevant literature sources, then analyzed using content analysis techniques. The results show that the use of AI can increase the effectiveness of Islamic education learning when integrated with spiritual and humanistic values. This integration strategy is carried out through strengthening the role of teachers as moral guides, developing ethics-based digital literacy, and implementing humanistic learning based on Islamic values. Thus, the use of AI in Islamic education needs to be directed to create a balance between technological advancements and the formation of students' religious character.